2023
DOI: 10.3390/catal13101346
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Electrocatalysts for the Oxygen Evolution Reaction: From Single- to Multielement Materials

América Higareda,
Diana Laura Hernández-Arellano,
Luis Carlos Ordoñez
et al.

Abstract: The proton exchange membrane water electrolyzer (PEM-WE) is a well-known green technology for hydrogen production. The main obstacle to its development, on a large scale, is the sluggish kinetics of the oxygen evolution reaction (OER). At present, the design of acid-stable electrocatalysts with low overpotential and excellent stability for the OER constitutes an important activity in electrocatalysis. This review presents an analysis of the fundamentals and strategies for the design of advanced electrocatalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…It has been noted from the literature that the modulated electronic states and surface electronic oxidation states of the cations are important in enhancing the OER activity of the catalysts [41]. Thus, the modulated electronic states in the form of oxygen vacancies could enhance the water adsorption and dissociation kinetics of the intermediates and the active metal sites [42]. In this study, it was observed that the oxidation states of the Mn cation were modified due to the A-site doping with various lanthanide series metals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noted from the literature that the modulated electronic states and surface electronic oxidation states of the cations are important in enhancing the OER activity of the catalysts [41]. Thus, the modulated electronic states in the form of oxygen vacancies could enhance the water adsorption and dissociation kinetics of the intermediates and the active metal sites [42]. In this study, it was observed that the oxidation states of the Mn cation were modified due to the A-site doping with various lanthanide series metals.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical water splitting can produce sustainable hydrogen (H 2 ) and oxygen (O 2 ) as a cleaner alternative to fossil fuels for energy conversion and storage [1]. Thereinto, the relatively high overpotential and slow reaction kinetics for OER reaction significantly impede the overall electrolysis efficiency [2]. In addition, Zn-air batteries (ZABs) with high theoretical specific energy density (1086 Wh kg À 1 ), low cost, and good safety are competitive among the various storage devices.…”
Section: Introductionmentioning
confidence: 99%
“…To take the NO 3 RR a step further, it is essential to consider the accompanying oxygen evolution reaction (OER) at the anode in the full cell (NO 3 RR-OER) electrolysis. The sluggish kinetics of OER due to high energy demand for O–O bond formation (4e – transfer) become the bottleneck for the effective synthesis of NH 3 . Alternatively, substituting the OER at the anode by other thermodynamically more feasible oxidation reactions, viz., the glucose oxidation reaction (GOR), thus decreases an energy input for ammonia synthesis along with the value-added products at the anode (NO 3 RR-GOR). This strategy provides a proficient assimilation of two industrially important areas, i.e., anodic oxidation of glucose to glucaric/gluconic acid along with enhanced ammonia production at the cathode while lowering the overall potential, subsequently increasing its economic value.…”
mentioning
confidence: 99%